Association Among Internal Assets, Bullying, and Emotional Distress in Eighth Grade Students. (2nd October 2019) - Fredkove, Windy M.; Gower, Amy L.; Sieving, Renee E.
ABSTRACT: BACKGROUND: Adolescents are in a unique developmental stage, ideal for initiating healthy behaviors and benefiting from health promotion interventions. In this study, we used positive youth development and resilience frameworks, to investigate the role of internal assets as a protective factor for bullying and emotional distress among early adolescents, with attention to whether those associations vary by sex. METHODS: This is a secondary analysis of the 2013 Minnesota Student Survey, a cross‐sectional, population‐based survey of Minnesota youth. Participating eighth grade students (N = 42, 841) reported on internal assets, physical, relational and cyberbullying involvement, and emotional distress. RESULTS: Logistic regression analyses, stratified by sex and controlling for sociodemographic characteristics, revealed that students with higher internal assets had lower odds of all forms of bullying victimization and perpetration than those with lower internal assets. Higher levels of internal assets were also associated with lower odds of emotional distress. All associations were significant for boys and girls, but appeared stronger for girls. CONCLUSIONS: Findings indicate that internal assets may buffer young teens from bullying and from the emotional distress that may result from bullying involvement. Approaches bolstering internal assets may be beneficial for combating bullying and emotional distress during early adolescence.